THE PSYCHOLOGICAL CHARACTERISTICS AND CLASSIFICATION CRITERIA OF CRIMINAL GROUPS - Aghabekyan, A. A.; Harutyunyan, A. K. (Modern Psychology, 2019)
The legal classification of crimes is briefly described in the article, it is noted that, unlike unscrupulous crimes, group crime can never be considered casual as it is prethought and occasionally officials may be involved in such groups assuming the roles of participants on one hand and the roles of leaders on the other hand.